Pipeline rules of thumb handbook : quick and accurate solutions to your everyday pipeline problems - McAllister, E. W. (Gulf Professional/Elsevier, 2009)
This classic reference has built a reputation as the "go to" book to solve even the most vexing pipeline problems. Now in its seventh edition, Pipeline Rules of Thumb Handbook continues to set the standard by which all others are judged. The 7th edition features over 30% new and updated sections, reflecting the exponential changes in the codes, construction and equipment since the sixth edition. The seventh edition includes: recommended drill sizes for self-tapping screws, new ASTM standard reinforcing bars, calculations for calculating grounding resistance, national Electrical Code tables, Corilis meters, pump seals, progressive cavity pumps and accumulators for lubricating systems. * Shortcuts for pipeline construction, design, and engineering * Calculations methods and handy formulas * Turnkey solutions to the most vexing pipeline problems